1978
DOI: 10.1111/j.1365-2923.1978.tb00494.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of short and multiple choice questions in the evaluation of students of biochemistry

Abstract: Summary Premedical and other undergraduate students were given an examination consisting of a section of short questions and a section of multiple choice questions of the one in five type. After correction for random guessing, the average multiple choice mark was close to the average short question mark. Thus the theoretical ‘average’ student did equally well in both types of examination. Individual multiple choice marks were plotted against the corresponding short question mark. Although the two sets of marks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
2

Year Published

1980
1980
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
3
2
Order By: Relevance
“…Forsdyke (1978), comparing results of multiple‐choice and short essay questions in biochemistry examinations reported no significant difference between the two. With more experience with practical and short essay items, our students would probably give a similar result.…”
Section: Resultscontrasting
confidence: 98%
See 2 more Smart Citations
“…Forsdyke (1978), comparing results of multiple‐choice and short essay questions in biochemistry examinations reported no significant difference between the two. With more experience with practical and short essay items, our students would probably give a similar result.…”
Section: Resultscontrasting
confidence: 98%
“…Furthermore, plots of the scores of individual sections versus the criterion and calculations of the respective best‐fit least‐squares lines showed that different parts of the student population (above and below average relative to the criterion) were not significantly advantaged or disadvantaged by the different item types. These results are not in agreement with those published by Forsdyke (1978). Construct validity . Evidence confirming the presence of constructs that were identified with each of the examination sections but also contributed to the general construct—achievement in pathology—was required.…”
Section: Evidence Of Validitycontrasting
confidence: 99%
See 1 more Smart Citation
“…For example, one's knowledge influences one's perception of one's environment (selective attention). The fact that cues can facilitate retrieval (Forsdyke, 1978), suggests that often the factor limiting retrieval is the retrieval process itself, rather than presence in the store.…”
Section: Terminology In Long Term Memory Researchmentioning
confidence: 99%
“…The multiple choice question (MCQ) is well established and widely used in a large number of medical schools and it is considered by many examiners to be an effective method of assessment. The MCQ has many advantages over the conventional essay question, and there has been evidence to show a high degree of correlation between MCQ and short answer question performance (Forsdyke, 1978). There are also disadvantages (Newble, Baxter & Elmslie, 1979).…”
Section: Introductionmentioning
confidence: 99%